AESTHETIC REHABILITATION OF MAXILLARY AND MANDIBULAR HOPELESS TEETH WITH IMMEDIATE REMOVABLE PARTIAL DENTURE - Afif Surya Adena; Endang Wahyuningtyas; Intan Ruspita (Dentino : Jurnal Kedokteran Gigi, 2021)
ABSTRACTBackground: Edentulism post tooth extraction is an undesirable state among patients, specifically with the involvement of anterior dentition. Immediate denture in cases of anterior teeth extraction is a selected treatment to recover aesthetic and phonetic function. This treatment shows an impact on psychological stability and improves patients’ confidence level. Objective: This case report provides information on the management of immediate removable partial denture for maxillary and mandibular teeth. Case: A female teacher suffered from tooth loss of 26, 28, 36, 46, 47. Tooth 11, 14, 21, 22, 31, 32, 41, 42 were not supported with adequate periodontal tissue and presented with level 3 tooth mobility. Patient expected the teeth to be removed and managed with prosthodontic appliance, yet disfavoring the stage of edentulism because her profession demanded high social performance. Case management: The treatment for this case includes immediate removable partial denture with acrylic material in upper and lower jaw. Denture was fabricated prior to the extraction of tooth 11, 14, 21, 22, 31, 32, 41, 42, and inserted promptly. The insertion result showed good occlusion, retention, stabilization, and tissue adaptation of denture. It also demonstrated good aesthetic result. On 24 hours control post insertion, wound closure was gradually established with the presence of redness. A week after insertion, wounded tissue had been fully covered and redness had been diminished. Conclusion: Immediate removable partial denture provides good aesthetic and function. Patient was satisfied with the treatment because it improved her appearance without experiencing any period of edentulism.Keywords: Aesthetics, Edentulous, Extraction, Immediate Removable Partial Denture.